A theoretical analysis of the energy absorption response of expanded metal tubes under impact loads. (November 2017) - Hatami, H.; Rad, M. Shokri; Jahromi, A. Ghodsbin
Highlights: Expanded metal tube with α = 0, have higher η and SEA and the symmetric collapse. Increasing the H of drop hammer would increase the Xcrushing, Fmean, Fpeak and Ea. Analytical model can draw the force-displacement curve during dynamic loading. Abstract: In this study, cylindrical absorbers made of expanded metal structures subjected to impact loading were investigated. Experimental, numerical, and analytical approaches were employed for the analysis. Studied absorbers were made of unit cells with different angles. Experiments were performed using a drop hammer. Numerical analysis was accomplished using Abacus finite element software. Energy Method was applied for analytical study. Based on the results obtained in this study, the absorber with cell angle of α = 0° had symmetric collapse. For α = 30° and 45°, the point buckling had occurred. In addition, full buckling had occurred in the structure with α = 90°. The amount of crush resulting from different drop heights were also compared. Increase in the drop height of the hammer would increase the crush length, average force, and amount of energy absorption. In the analytical phase, using the energy method, a system of equations was achieved; which led to a force-displacement graph which can determine the behavior of the expanded metal cylindrical absorber with changes in the geometrical parameters and mechanical properties.